Routine Drainage of Colorectal Anastomoses: An Evidence-Based Review of the Current Literature - Sameh Hany Emile; Tito M. Abd El-Hamed (Gastroenterology Research and Practice)
Background. The use of prophylactic drainage after colorectal anastomoses has been long debated. This report aimed to review the current literature discussing routine drainage of colorectal anastomoses highlighting two opposite perspectives (prodrainage and antidrainage) to demonstrate the clinical utility of prophylactic drainage and its proper indications. Methods. An organized literature search was conducted querying electronic databases and Google Scholar. Articles evaluating the role of routine prophylactic drainage after colorectal anastomosis were included and divided into two categories: articles supporting the use of drains (prodrainage) and articles disputing routine drainage (antidrainage). Results. There were seven systematic reviews and/or meta-analyses, one Cochrane review, one randomized controlled trial, and six prospective or retrospective cohort studies. Six studies supported prophylactic drainage of colorectal anastomoses; the quality of these studies ranged between grade II and IV. Nine studies recommended against the use of prophylactic drainage, six studies were grade I, one was grade II, and two were grade IV. Conclusion. Since level I evidence studies including well-designed randomized trials and meta-analyses recommended against the use of pelvic drainage as a routine practice after colorectal anastomoses, we conclude no significant impact of routine drainage on the risk of anastomotic leakage after colorectal anastomoses.